Evolution, retreat or rejection: Brazil's, India's and China's normative stances on R2P. Issue 3 (2nd July 2016) - Job, Brian L
Abstract: This paper outlines the development and evolution of the normative positions of China, Brazil and India on issues surrounding the responsibility to protect (R2P) by charting their engagement in the 'institutionalized conversation' within the United Nations. In doing so, it seeks to dispel characterizations of these states as having adopted individual or common positions that either wholly reject or accept R2P. The nuances of the adaption and adoption of their postures need to be appreciated. Indeed, of the three component 'pillars' of R2P, they find themselves in general accord regarding Pillar One (state responsibility) and Pillar Two (prevention and assistance). It is on Pillar Three (reaction and response) that they diverge from each other and find themselves most at variance with 'Western' agendas of intervention and regime change. This divergence is most sharply drawn at present, in light of the Libyan and ongoing Syrian experiences.